Linking social system failures: A short note on marriage and firm failure - Ingmar Zanger; Sidhartha S. Padhi; Stephan M. Wagner (Journal of Innovation & Knowledge (JIK), 2018)
This study examined social system failures and sought to identify a plausible mechanism behind these failures. Stretched exponential distributions were observed for failure of marriages in the US, UK, and Germany. In addition, the study provides evidence of power laws in the failure of large firms in the US and worldwide. Summation of stretched exponentials leads to power laws, so an underlying principle can be established to link different types of social system failures such as failures of marriages and firms. The generation of these fat-tailed distributions in social system failures can be explained by Zipf's principle of least effort. Therefore, increasing initial efforts at the individual level through marriage counseling or stakeholder synchronization should reduce failures.
Keywords: L; M; 650; Firm failure; Organizational failure; Divorce; Power laws; Stretched exponential distribution